Training And Innovation In Vocational Education Can Contribute To Economic Growth - LILIK SULISTYO (International Conference on Industrial Revolution for Polytechnic Education, 2019)
Vocational education and training (VET) has in recent years enjoyed a revival for twomajor reasons. Firstly, it is regarded as a suitable means of promoting economic growth.Secondly, it is seen as a potentially powerful tool for fostering social inclusion. In thisreview, these assumed effects are critically examined on the basis of the vastly expandingliterature in the field. Evidence of the productivity‐enhancing effects of VET at companylevel is quite solid, but evidence of the effect on overall economic growth is far fromconclusive. The effects on social inclusion are uncertain because reform of VET systemshas not been sufficient and because it has proved difficult to bring about the necessaryinstitutional change. The review identifies policy implications and makes somesuggestions for future research.